Oral Tradition as Indigenous Arts Pedagogy: Transmitting Moral Values through Narrative Performance - Manggau, Arifin; Jayadi, Karta; Ismail, Alice Sabrina; Prusdianto, Prusdianto (Universitas Negeri Semarang, 2025)
This study explores the inheritance patterns and educational significance of Iyabelale, a traditional Bugis lullaby, as a medium for character building and cultural preservation. Against the backdrop of globalisation and digital transformation, this study aims to assess the symbolic structure, cultural function, and pedagogical relevance of Iyabelale in the Bugis community. Using a qualitative ethnographic case study approach, data were collected through interviews, observations, and documentation in rural and urban settings in South Sulawesi. The findings of this study reveal that Iyabelale functions as a multidimensional cultural artefact, conveying values such as empathy, responsibility, and spiritual awareness through its metaphorical language and melodic structure. Although its delivery has been weakened by technological shifts and changes in family structures, the lullaby remains a potential tool for culturally grounded character education. Integrating Iyabelale into modern curricula through community collaboration and digital innovation can foster emotional bonds, cultural identity, and moral learning. This study contributes to the growing knowledge about indigenous oral traditions and offers practical pathways for revitalisation in contemporary educational contexts.